My side of the mountain - George, Jean Craighead, 1919- (New York : Dutton Children's Books, 1959)
A young boy relates his adventures during the year he spends living alone in the Catskill mountains, including his struggle for survival, his dependance on nature, his animal friends, and his ultimate realization that he needs human companionship.
Keywords: Survival -- Fiction; Self-reliance -- Fiction; Mountain life -- Fiction